Evaluasi Kualitas Penggunaan Website Mata Kuliah Bahasa Inggris Berdasarkan ISO/IEC 25010:2011 pada Universitas Universal - Rama Vito; William Sanjaya; Jason; Andy Santoso; Holong Marisi Simalango (Media Informatika, 2021)
This study was about the evaluation of the quality of Edmodo English website at Universal University (UVERS) in Batam City in Riau Islands using ISO/IEC 25010:2011. Edmodo UVERS website is a student website of Universal University that serves as a learning media around lectures. The purpose of the research with the use of ISO/IEC 25010:2011 is to provide recommendations in improving the quality of the Edmodo UVERS website. The methodology used is the observation and dissemination of questionnaires to users of the website both students and lecturers consisting of more than 30 responses. The questionnaire consists of seven points namely usability, information quality, interaction quality, effectiveness and efficiency, satisfaction, risk-free, and covers the whole. The conclusion obtained is that the recommendations given are in the usability factor, satisfaction in reliability factors, effectiveness & efficiency in perfomance efficiency factors, and risk-free on reliability factors